2016
DOI: 10.3389/fimmu.2016.00514
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of Suppressor of Cytokine Signaling-1 Regulates Local Immunity in the Lung

Abstract: Suppressor of cytokine signaling 1 (SOCS1) is a negative feedback inhibitor of cytoplasmic Janus kinase and signal transducer and activator of transcription (STAT) signaling. SOCS1 also contains a nuclear localization sequence (NLS), yet, the in vivo importance of nuclear translocation is unknown. We generated transgenic mice containing mutated Socs1ΔNLS that fails to translocate in the cell nucleus (MGLtg mice). Whereas mice fully deficient for SOCS1 die within the first 3 weeks due to excessive interferon si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In patients with severe asthma, decreased SOCS1 expression correlated with eosinophilia and Th2-driven inflammation ( 28 ). Furthermore, mice with a selective knockout of the nuclear localization sequence (NLS) of SOCS1 presented with low-grade pulmonary inflammation and an increase in Th2-type cytokines ( 13 ). In our patients Th2-type cytokines in CD4+ T cells were not elevated as compared to healthy controls, emphasizing the importance of local effects such as inflammation of SOCS1 in different tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with severe asthma, decreased SOCS1 expression correlated with eosinophilia and Th2-driven inflammation ( 28 ). Furthermore, mice with a selective knockout of the nuclear localization sequence (NLS) of SOCS1 presented with low-grade pulmonary inflammation and an increase in Th2-type cytokines ( 13 ). In our patients Th2-type cytokines in CD4+ T cells were not elevated as compared to healthy controls, emphasizing the importance of local effects such as inflammation of SOCS1 in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this particular function of SOCS1, other investigations suppose that SOCS1 impacts on multiple immune pathways beyond enhanced signal transducer and activator of transcription (STAT) 1 phosphorylation ( 13 15 ) ( Figure 1A ) . SOCS1 additionally functions as an E3 ligase substrate ( 16 ): SOCS1 binds to ElonginB/C via interaction of the C-terminal SOCS-box domain, to form a Cullin5 Rbx2 E3 ligase complex ( 12 ) ( Figure 1B ).…”
Section: Introductionmentioning
confidence: 99%
“…SOCS1 is known to regulate Th2‐cytokine signaling in both in‐vitro cell cultures and in‐vivo mouse models. It blocks the phosphorylation of STAT6 through inhibiting JAK activity, and has been identified as a negative feedback regulator of the JAK/STAT6 pathway . Mucosal SOCS1 is increased in patients with AR and asthma compared with healthy controls .…”
Section: Discussionmentioning
confidence: 99%
“…Zimmer et al adopted an elegant tool to study the nucleus-located SOCS1 by replacing its NLS. They found that mice lacking nuclear SOCS1, but not cytoplasmic SOCS1, do not have neonatal lethal symptoms, but have mild airway inflammation, indicating different roles of nucleus located and cytoplasm located SOCS1 (65).…”
Section: Socs1 Deficiencymentioning
confidence: 99%